Turn of the month effect in the South African equity market: A GARCH analysis: Array - Mazviona, Batsirai; Mah, Gisele; Choga, Ireen (Acta Universitatis Danubius. Œconomica, 2021)
Understanding calendar patterns assist in identification of stock market return drivers and investment decision making. The objective of the study was to determine whether turn of the month effect exists in the South African equity market. Financial data for Johannesburg Stock Exchange (JSE) indices covers the period 1995-2018. Ten JSE indices namely Top 40, All Shares, Basic Materials, Industrials, Consumer Goods, Health Care, Consumer Services, Telecommunications, Financials and Technology were analysed. Logarithm returns were used in turn of the month seasonality modelling. The Generalized Auto Regressive Conditional Heteroskedasticity Model (GARCH), exponential GARCH (EGARCH) and threshold GARCH (TGARCH) models are used to model turn of the month anomaly. Models were implemented in R and Eviews software. The mean equation results of the turn of the month examination displayed a positive effect for the Top 40 and All Shares aggregate indices. Similarly, a positive turn of the month effect was observed in the Basic materials, Consumer goods, Health care, Consumer services, Financials, Technology, Industrials, and Telecommunications sectors. The variance equation showed no turn of the month effect in the Top 40 and All Shares indices, though the Basic materials sector indicated a positive turn of the month effect. For the turn of the month strategy, investing in the Telecommunications sector offers the highest returns to investors. Investors should avoid investing in the Basic materials sector as it increases their exposure. The existence of the turn of the month effect nullifies the efficient market hypothesis in the South African equity market. In contrast with previous studies, we add value by analysing turn of the month effect sectorial indices for a largest African stock market.